2017
DOI: 10.1186/s12889-017-4408-3
|View full text |Cite
|
Sign up to set email alerts
|

The association between time scarcity, sociodemographic correlates and consumption of ultra-processed foods among parents in Norway: a cross-sectional study

Abstract: BackgroundUse of ultra-processed foods has expanded rapidly over the last decades and high consumption has been positively associated with risk of e.g. overweight, obesity and type 2 diabetes. Ultra-processed foods offer convenience as they require minimal time for preparation. It is therefore reasonable to assume that such foods are consumed more often among people who experience time scarcity. The main aim of this study was to investigate the association between time scarcity and consumption of ultra-process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 44 publications
7
83
1
4
Order By: Relevance
“…Current lifestyles have influenced dietary habits from a diet based on fresh and minimal processed foods to another with high consumption of processed and ultra-processed foodstuffs [ 33 ]. Nowadays, due to the parent’s lack of time, children end up eating ultra-processed and fast foods on a regular basis [ 34 ].…”
Section: Newer Is Not Always Bettermentioning
confidence: 99%
“…Current lifestyles have influenced dietary habits from a diet based on fresh and minimal processed foods to another with high consumption of processed and ultra-processed foodstuffs [ 33 ]. Nowadays, due to the parent’s lack of time, children end up eating ultra-processed and fast foods on a regular basis [ 34 ].…”
Section: Newer Is Not Always Bettermentioning
confidence: 99%
“…Ultra-processed food purchasing and consumption patterns have been described in several countries [4], with studies in Brazil [17, 32-35], Chile [16, 36], Colombia [37], Indonesia [38], Kenya [39], multiple European countries [9, 40], France [41], Norway [42, 43], Sweden [44], Australia [45, 46], New Zealand [47], USA [19, 20, 48, 49], Canada [18, 50, 51], and the UK [15, 40, 52]. …”
Section: Introductionmentioning
confidence: 99%
“…Gender had no significant association with the consumption of ultra-processed foods since several studies have shown differing results for gender and the association with ultra-processed foods. According to Djupegot et al (2017), men more commonly consume ultra-processed foods compared to women; however, a study by Simões et al (2018) shows the opposite finding, proving that gender has no association with the consumption of ultra-processed foods.…”
Section: Association Between Energy Contribution Of Ultraprocessed Fomentioning
confidence: 95%